Effects of temporal fluctuation in population processes of intertidal Lanice conchilega (Pallas, 1766) aggregations on its ecosystem engineering. (15th March 2017) - Alves, Renata M.S.; Vanaverbeke, Jan; Bouma, Tjeerd J.; Guarini, Jean-Marc; Vincx, Magda; Van Colen, Carl
Abstract: Ecosystem engineers contribute to ecosystem functioning by regulating key environmental attributes, such as habitat availability and sediment biogeochemistry. While autogenic engineers can increase habitat complexity passively and provide physical protection to other species, allogenic engineers can regulate sediment oxygenation and biogeochemistry through bioturbation and/or bioirrigation. Their effects rely on the physical attributes of the engineer and/or its biogenic constructs, such as abundance and/or size. The present study focused on tube aggregations of a sessile, tube-building polychaete that engineers marine sediments, Lanice conchilega . Its tube aggregations modulate water flow by dissipating energy, influencing sedimentary processes and increasing particle retention. These effects can be influenced by temporal fluctuations in population demographic processes. Presently, we investigated the relationship between population processes and ecosystem engineering through an in-situ survey (1.5 years) of L. conchilega aggregations at the sandy beach of Boulogne-sur-Mer (France). We (1) evaluated temporal patterns in population structure, and (2) investigated how these are related to the ecosystem engineering of L. conchilega on marine sediments. During our survey, we assessed tube density, demographic structure, and sediment properties (surficial chl- a, EPS, TOM, median and mode grain size, sorting, and mud and water content) on a monthly basis for 12 intertidal aggregations. We found that the population was mainly composed by short-lived (6–10 months), small-medium individuals. Mass mortality severely reduced population density during winter. However the population persisted, likely due to recruits from other populations, which are associated to short- and long-term population dynamics. Two periods of recruitment were identified: spring/summer and autumn. Population density was highest during the spring recruitment and significantly affected several environmental properties ( i.e. EPS, TOM, mode grain size, mud and water content), suggesting that demographic processes may be responsible for periods of pronounced ecosystem engineering with densities of approx. 30 000 ind·m −2 . Highlights: The intertidal L. conchilega aggregations recruit twice per year at Boulogne. The first recruitment in spring is characterized by abundant, very small animals. The second recruitment in autumn is characterized by less abundant, larger animals. L. conchilega engineers its habitat more pronouncedly during spring recruitment.